Molecular basis of muscle hypertrophy and atrophy: Potential therapy for muscular dystrophy - Naoki Ito; Yuko Miyagoe-Suzuki; Shin'ichi Takeda (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Skeletal muscle mass is regulated by a balance of protein synthesis and degradation. The regulation of this protein synthesis/degradation system is linked with muscle activity, and leads to muscle hypertrophy/atrophy. However, recent studies suggested that this system is also linked to the mechanisms underlying muscular dystrophy. In this review, we summarize the recent advances relating to the molecular mechanisms of the protein synthesis/degradation system, and overview the new therapeutic strategy for muscular dystrophy that targets the molecular events that regulate muscle hypertrophy/atrophy.